2018
DOI: 10.20517/2574-1225.2018.30
|View full text |Cite
|
Sign up to set email alerts
|

Functional results and quality of life after transanal total mesorectal excision

Abstract: This is a narrative review on ano-rectal, sexual, urinary, and quality of life outcomes after transanal total mesorectal excision (TME). Little is known on this topic as only a few studies are currently available in the literature. According to these, it appears that the functional results and quality of life are not substantially impaired compared with standard TME. However more data are needed to precisely assess the outcomes of this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…A wide range of data is available on the quality of life (QoL) after TaTME. Initial studies showed worse shortand mid-term functional results, but most of the subsequent studies showed comparable results between the different minimally invasive TME procedures (6)(7)(8)(9). There is no clear data that prove advantage or disadvantage of TaTME over rTME or laparoscopic TME in terms of functional results (6,(10)(11)(12).…”
Section: Introduction Introductionmentioning
confidence: 99%
“…A wide range of data is available on the quality of life (QoL) after TaTME. Initial studies showed worse shortand mid-term functional results, but most of the subsequent studies showed comparable results between the different minimally invasive TME procedures (6)(7)(8)(9). There is no clear data that prove advantage or disadvantage of TaTME over rTME or laparoscopic TME in terms of functional results (6,(10)(11)(12).…”
Section: Introduction Introductionmentioning
confidence: 99%
“…Given these differences, a difference in the incidence and severity of functional postoperative outcomes is possible. This is possible due to the prolonged perioperative insertion of an anal platform, sphincter-complex damage 15 and the construction of very low anastomoses with TaTME 16 . However, the majority of studies included in this meta-analysis were characterized by a large heterogeneity in important factors such as tumour height and time of follow-up 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Yellinek and Wexner [4] , writing from the Cleveland clinic, discuss an alternative to the robot, namely transanal total mesorectal excision (TaTME), the importance of a registry and training programme though conclude that the single port robot may provide a method for better adopting this technique, potentially as a combined approach and ongoing trial data is awaited. De Nardi [5] suggests that TaTME has comparable functional outcomes compared with the abdominal approach though the COLOR III trial results are eagerly awaited to assess this.…”
mentioning
confidence: 99%